2022
DOI: 10.1111/nph.18539
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity across forest vertical profiles: patterns, mechanisms, and ecological implications

Abstract: Rising temperatures are influencing forests on many scales, with potentially strong variation vertically across forest strata. Using published research and new analyses, we evaluate how microclimate and leaf temperatures, traits, and gas exchange vary vertically in forests, shaping tree, and ecosystem ecology. In closed-canopy forests, upper canopy leaves are exposed to the highest solar radiation and evaporative demand, which can elevate leaf temperature (T leaf ), particularly when transpirational cooling is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 340 publications
(513 reference statements)
2
38
0
Order By: Relevance
“…Coffee plants cultivated under HS and LS had differences in leaf traits similar to those expected in sun and shade leaves (Vinod et al 2022), and previously reported for coffee (Matos et al 2009;Moraes et al 2010). Generally, coffee leaves from plants grown in LS had a larger LA, SLA, and a lower na st (Table 1).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Coffee plants cultivated under HS and LS had differences in leaf traits similar to those expected in sun and shade leaves (Vinod et al 2022), and previously reported for coffee (Matos et al 2009;Moraes et al 2010). Generally, coffee leaves from plants grown in LS had a larger LA, SLA, and a lower na st (Table 1).…”
Section: Discussionsupporting
confidence: 80%
“…Acclimation to full sunlight promotes leaf traits that reduce leaf temperature, while shade acclimation promotes traits that maximize light capture (Vinod et al 2022). Sun leaves are generally smaller in size and thicker, with higher leaf mass to area (LMA), (or lower specific leaf area -SLA), and higher stomatal density to meet demand for cooling, whereas shade leaves have the opposite traits (Zwieniecki et al 2004;Vinod et al 2022). For coffee, these leaf traits significantly differ in plants growing under shade or in full sunlight (Matos et al 2009;Moraes et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For a tree canopy model, it is necessary to consider that assimilation and transpiration rates vary within the crown (Lalic et al., 2013; Lalic & Mihailovic, 2004; Vinod et al., 2022). This variation is caused by two factors: (a) leaves are not uniformly distributed within the crown, (b) the solar radiation becomes attenuated on its way through the crown because the leaves shade each other.…”
Section: Methodsmentioning
confidence: 99%
“…For example, moose seek taller and denser vegetation to avoid high summer temperatures (Melin et al, 2014), and arboreal animals track their thermal niche by moving vertically through vegetation, often seeking out tree cavities or denser vegetation during the hottest hours of the day (Scheffers et al, 2017; Scheffers & Williams, 2018). Microclimates vary by ecosystem type, with open woodlands yielding greater diurnal variation in temperature and tall, closed canopy forests reducing temperature extremes below the canopy (De Frenne et al, 2019, 2021; Jucker et al, 2018; Vinod et al, 2023). Canopy gap openings (e.g.…”
Section: How Vegetation Structure Influences Animal Behaviourmentioning
confidence: 99%